2020
DOI: 10.1016/j.biotechadv.2020.107636
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of human mesenchymal stem/stromal cells (hMSCs) in bioreactors using microcarriers: lessons learnt and what the future holds

Abstract: Human mesenchymal stem/stromal cells (hMSCs) present a key therapeutic cellular intervention for use in cell and gene therapy (CGT) applications due to their immunomodulatory properties and multi-differentiation capability. Some of the indications where hMSCs have demonstrated pre-clinical or clinical efficacy to improve outcomes are cartilage repair, acute myocardial infarction, graft versus host disease, Crohn's disease and arthritis. The current engineering challenge is to produce hMSCs at an affordable pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 180 publications
(371 reference statements)
0
33
0
Order By: Relevance
“…Cell and gene therapies (CGTs), such as human mesenchymal stem cells (hMSCs; Silva Couto et al 2020) and CAR-T cells (Wang and Rivière 2016), present a novel therapeutic modality to treat a range of chronic, age-related conditions and address current unmet clinical need. Despite their clinical promise, however, currently approved CGTs suffer from a lack of scalable manufacture, high costs ([ $150,000 per dose), poorly defined manufacturing processes and a lack of effective small-scale models to support process development activity (Vormittag et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cell and gene therapies (CGTs), such as human mesenchymal stem cells (hMSCs; Silva Couto et al 2020) and CAR-T cells (Wang and Rivière 2016), present a novel therapeutic modality to treat a range of chronic, age-related conditions and address current unmet clinical need. Despite their clinical promise, however, currently approved CGTs suffer from a lack of scalable manufacture, high costs ([ $150,000 per dose), poorly defined manufacturing processes and a lack of effective small-scale models to support process development activity (Vormittag et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Scaling up of stem cells and progenitors can be performed using three different strategies: 1) monolayer cultures, 2) culturing cells on microspheres and 3) organoid/spheroid production ( Silva Couto et al, 2020 ). Monolayer cultivation is the least effective method.…”
Section: Introductionmentioning
confidence: 99%
“…We found that a ramped agitation scheme enabled sphere formation at the beginning of the run and limited cell settling throughout the run. The use of ramped agitation to keep the Discogenic Cell spheres in suspension differs from the predominate use of magnetic levitation or viscous carriers to grow cell spheres described previously [ 1 , 21 , 25 ].…”
Section: Discussionmentioning
confidence: 99%